Acoustic Wave Reflection Control Based on Broadband Differential Phase Shifters - Qin, Zifu; Liu, Xiaohan; Ma, Chu (Frontiers in Mechanical Engineering, 2021)
Controlling the flow of acoustic waves has broad applications in acoustic imaging, communication, energy harvesting, audio systems, etc. Metasurfaces have been developed for wave control. In this work we propose the design of broadband differential phase shifters for acoustic reflected waves, which can achieve nearly constant phase shift values over a broad frequency ranges. We further demonstrate the design of a broadband differential $π$ phase shifter that works in the frequency range of [10 KHz, 16 KHz] and its applications in acoustic metasurfaces for steering and focusing of reflected acoustic waves. The metasurfaces we designed have the following advantages: 1) The metasurface is formed with binary patterns instead of more complex phase discretization steps, thus the metasurface realization is less complex for fabrication and assembly. \textcolor{blue}{2) The phase shift values of the two basic phase shifter elements are broadband, thus we do not need to fabricate new elements for each frequency. Rearranging the same elements into different location patterns would allow us to tune the working frequency of the metasurfaces. }